2002
DOI: 10.1051/0004-6361:20021029
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared spectrum of the zodiacal light observed with ISOPHOT

Abstract: Abstract. We present 29 mid-infrared spectra of the zodiacal light distributed over the sky. The observed 5.9-11.7 µm spectral shapes are well represented by blackbody radiation with colour temperatures in the range of 255 ≤ T ≤ 300 K. The spectra are smooth and featureless. The variation of the temperature can be explained by the geometrical distribution of dust in the inner solar system. This result indicates that although the interplanetary dust particles originate from discrete sources (comets, asteroids) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…It also agrees with infrared observations showing silicates emission features (see e.g. Reach et al 1996;Leinert et al 2002), with the analysis of the IDPs collected in the stratosphere of the Earth and micrometeorites collected in ices (for a review, see Jessberger et al 2001) and with recent analyses of Stardust samples (see e.g. Zolensky et al 2006;Sandford et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…It also agrees with infrared observations showing silicates emission features (see e.g. Reach et al 1996;Leinert et al 2002), with the analysis of the IDPs collected in the stratosphere of the Earth and micrometeorites collected in ices (for a review, see Jessberger et al 2001) and with recent analyses of Stardust samples (see e.g. Zolensky et al 2006;Sandford et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…But we do not. Leinert et al (2002) found that the ZE spectra at various ecliptic latitudes observed by ISOPHOT are not significantly deviated from blackbody SEDs in the wavelength range from 6 to 12 μm. They concluded that the IPDs are well mixed over the IPD cloud.…”
Section: Discussionmentioning
confidence: 81%
“…In the mid-IR wavelength range, the background brightness is dominated by the ZE (Leinert et al 1998). The spectral energy distribution (SED) of ZE is described by that of a blackbody (Ootsubo et al 1998;Leinert et al 2002;Reach et al 2003). Hence, the background brightness is assumed to follow the blackbody-type SED…”
Section: The Irc All-sky Surveymentioning
confidence: 99%
“…We find an average total zodiacal irradiance of 5. . It is plausible that the Sellers (1965) estimate did not consider the component of infrared emission from the dust grains due to a lack of emission measurements until the 1970s (Leinert et al 2002). However, we note that our method of scaling the scattered and emitted components based on measurements at two wavelengths could result in a larger integrated energy value.…”
Section: Zodiacal Irradiancementioning
confidence: 91%